Template-Free Synthesis of N-Doped Porous Carbon Materials From Furfuryl Amine-Based Protic Salts - Zhang, Yan; Wang, Jixia; Shen, Guohong; Duan, Junfei; Zhang, Shiguo (Frontiers in Chemistry, 2020)
Nitrogen-doped porous carbon materials (NPCMs) are usually obtained by carbonization of complicated nitrogen-containing polymers in the presence of template or physical/chemical activation of the as-synthesized carbon materials. Herein we reported the facile synthesis of NPCMs by direct carbonization of a series of furfuryl amine (FA)-based protic salts ([FA][X], X = NTf2, HSO4, H2PO4, CF3SO3, BF4, NO3, Cl) without any templates, tedious synthetic steps and other high techniques. The thermal decomposition of precursors and structure, elemental composition, surface atomic configuration, and porosity of carbons have been carefully investigated by thermogravimetric analysis (TGA), X-ray diffraction (XRD), Raman spectra, X-ray photoelectron spectroscopy (XPS), combustion elemental analysis, energy-dispersive spectrometry, and nitrogen isotherm adsorption. Different from the parent amine FA that was evaporated below 130 oC and no carbon was finally obtained, it was found that all the prepared protic precursors yield NPCMs. These carbon materials were found to exhibit anion structure- dependent carbon yield, chemical composition, and porous structure. The obtained NPCMs can be further exploited as adsorbents for dye removal and decoloration. Among all NPCMs, [FA][H2PO4]-derived carbon owing to its high surface area and special pore structure exhibits the highest adsorption capacities towards both Methylene blue and Rhodamine B.